Frontal eye field, where art thou? Anatomy, function, and non-invasive manipulation of frontal regions involved in eye movements and associated cognitive operations - Vernet, Marine; Quentin, Romain; Chanes, Lorena; Mitsumasu, Andres; Valero-Cabré, Antoni (Frontiers in Integrative Neuroscience, 2014)
The planning, control and execution of eye movements in 3D space relies on a distributed system of cortical and subcortical brain regions. Within this network, the Eye Fields have been described in animals as cortical regions in which electrical stimulation is able to trigger eye movements and influence their latency or accuracy. This review will focus on the Frontal Eye Field (FEF) a “hub” region located in Humans in the vicinity of the pre-central sulcus and the dorsal-most portion of the superior frontal sulcus. The straightforward localization of the FEF through electrical stimulation in animals is difficult to translate to the healthy human brain, particularly with non-invasive neuroimaging techniques. Hence, in the first part of this review, we will describe attempts made to characterize the anatomical localization of this area in the human brain. The outcome of functional Magnetic Resonance Imaging (fMRI), Magneto-encephalography (MEG) and particularly, non-invasive mapping methods such a Transcranial Magnetic Stimulation (TMS) will be described and the variability of FEF localization across individuals and mapping techniques will be discussed. In the second part of this review, we will address the role of the FEF. We will explore its involvement both in the physiology of fixation, saccade, pursuit and vergence movements and in associated cognitive processes such as attentional orienting, visual awareness and perceptual modulation. Finally in the third part, we will review recent evidence suggesting the high level of malleability and plasticity of these regions and associated networks to non-invasive stimulation. The exploratory, diagnostic and therapeutic interest of such interventions for the modulation and improvement of perception in 3D space will be discussed.